Gambaran Pengetahuan Ibu Tentang Pertolongan Pertama Kasus Tersedak pada Anak Usia Toddler di Desa Kedungwungu Kecamatan Anjatan Kabupaten Indramayu - Virgiani, Bestina Nindy; Irmawati, Novi Dwi; Nurjanah, Siti (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Choking is a very dangerous emergency. Choking mostly occurs at the age of three years and under because of the nature of exploring objects using the mouth. When a child is choking, quick and appropriate treatment is needed, especially for mothers who are with their children more often. The aim of this research was to determine the description of mothers' knowledge about first aid for choking cases in toddler-aged children in Kedungwungu Village. This type of research is quantitative descriptive. The research sample included 79 mothers who had children aged 1-3 years in Kedungwungu Village. The sample technique uses accidental sampling. The research instrument used a questionnaire. The analysis used is univariate. The results of the study showed that 44 (55.7%) respondents had sufficient knowledge of mothers regarding first aid for choking cases in toddlers, 26 (32.9%) respondents had good knowledge, and 9 (11.4%) respondents had poor knowledge about first aid. choked. This means that the mother's knowledge about first aid for choking cases in toddler-aged children is sufficient.